The Concept of Wealth in Islam and Confucianism and Its Implications for Life in This World and the Hereafter - Parjiman, Parjiman; Masruri, Siswanto; Hamsah, Ustadi (AL-ADYAN, 2026)
Wealth is a fundamental aspect of human life that relates to material, spiritual, and social well-being. Islam and Confucianism hold differing views on the concept of wealth and its implications for life in this world and the hereafter. This study aims to compare the concepts of wealth in Islam and Confucianism by highlighting theological principles, the ethics of wealth management, and their impact on the lives of individuals and society. The method employed is library research using a comparative approach, through an examination of classical and contemporary literary sources from both traditions. The research findings indicate that in Islam, wealth is viewed as a trust from Allah that must be acquired lawfully, managed responsibly, and utilized for the common good, as one will be held accountable for it in the afterlife. Meanwhile, in Confucianism, wealth is closely linked to the values of virtue and social balance, serving as a means to fulfill family responsibilities, including filial piety (孝/Xiào) and respect for ancestors. These differences influence the economic behavior of their adherents: Islam emphasizes social welfare and an orientation toward the afterlife, while Confucianism emphasizes family and social harmony. Nevertheless, both reject dishonesty and greed in the management of wealth.